2022
DOI: 10.3389/fpsyg.2022.967791
|View full text |Cite
|
Sign up to set email alerts
|

Affective touch in the context of development, oxytocin signaling, and autism

Abstract: Touch represents one of our most important senses throughout life and particularly in the context of our social and emotional experiences. In this review, we draw on research on touch processing from both animal models and humans. Firstly, we briefly describe the cutaneous touch receptors and neural processing of both affective and discriminative touch. We then outline how our sense of touch develops and summarize increasing evidence demonstrating how essential early tactile stimulation is for the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“…Given the considerable heterogeneity within the spectrum, future studies may benefit from including individuals with lower levels of functioning. Secondly, in light of our results, further investigation should address the well-known controversy surrounding the coexistence of both hypo-and hyper-autonomic sensory activation in the ASD population (Li et al, 2022), recognizing the observed dissociation between implicit and explicit levels of ASD experience. Thirdly, as in our study we obtained a sample composed of young ASD participants only, it would be important for future research to investigate the behavioral and autonomic activities related to affective touch in elderly subjects.…”
Section: Discussionmentioning
confidence: 82%
“…Given the considerable heterogeneity within the spectrum, future studies may benefit from including individuals with lower levels of functioning. Secondly, in light of our results, further investigation should address the well-known controversy surrounding the coexistence of both hypo-and hyper-autonomic sensory activation in the ASD population (Li et al, 2022), recognizing the observed dissociation between implicit and explicit levels of ASD experience. Thirdly, as in our study we obtained a sample composed of young ASD participants only, it would be important for future research to investigate the behavioral and autonomic activities related to affective touch in elderly subjects.…”
Section: Discussionmentioning
confidence: 82%
“…These findings support the conclusion that exogenously administered OT selectively facilitates neural and behavioral responses to stimulation of CT fibers during social touch via peripheral-mediated routes rather than by direct entry into the brain. Touch and massage interventions are increasingly demonstrated to have beneficial effects on brain development and function and it is likely that their effects on OT release and signaling play a major role in this ( Li et al, 2022 ). Our findings demonstrating that OT treatment can facilitate behavioral and brain responses to gentle social touch/massage therefore may have important translational therapeutic implications for using OT-based interventions in individuals with aberrant responses to social touch such as in autism.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, it has been demonstrated that OT acts synergistically with the dopaminergic afferents of the mesocorticolimbic regions and with the opioidergic tachykinin + neurons of the reward system and more specifically of the lateral and ventrolateral PAG [123,131,137,138].…”
Section: Ct Fibers Oxytocin System and Brain Developmentmentioning
confidence: 99%
“…Affective touch (AT) and the related CT fibers represent a fundamental functional system for the development of the newborn's brain and, according to some evidence, also for that of the fetus [121][122][123]. It is known that the somatosensory system is almost completely mature by the 32nd week of pregnancy, with the exception of the insula and the superior temporal sulcus, two cortical regions involved in social cognition that become operational around 2-3 months and 12 months of age respectively [123]. It is interesting to note that it has been hypothesized that already in this gestational period the CT fibers may have a regulatory function on the maturation and differentiation of the "affective tactile system".…”
Section: Ct Fibers Oxytocin System and Brain Developmentmentioning
confidence: 99%